Treatment of food processing industrial wastewater using two stages anaerobic system - Ibrahim, Muhammad Shahrul Shafendy (2014)
The wastewater produced by food manufacturing industry is known for its high concentration of COD and suspended solid. In wastewater treatment, anaerobic process is favorable due to its low cost, biogas production, low sludge production and more. In this study, upflow anaerobic sludge bed (UASB) and hybrid-UASB (HUASB) reactors, were combined with anaerobic filter (AF) bioreactors forming two stages system to treat food processing industry wastewater. This study was focused on the performance of UASB-AF (R1) and HUASB-AF (R2) treatment systems and the granules development. Seed sludge was deposited into HUASB column up to a third of the height. Palm oil shells were then packed into the HUASB (above seed sludge) as well as AF reactors to promote growth of microorganisms. The R1 and R2 systems were operated simultaneously, fed with raw food manufacturing wastewater taken from Azhar Food Manufacturing Factory. Parameters measured to evaluate the performance of the process were pH, COD, NH3-N, oil and grease and total phosphorus. The highest average COD removal efficiency, at 99%, were detected in R1 and R2 systems, both at OLR 10.56 g COD/L.d. Moreover, the presence of aggregated bio particles with diameter ranges from 2.934 to 5.00 mm were observed in both UASB and HUASB reactors. The highest percentage of 2.934 to 5.00 mm diameter granules were 7.6 % and 10.7% in the UASB and HUASB respectively. In addition, the highest removal rate coefficient, k values for UASB and HUASB were 2.1981 and 3.3950, occurred at OLR 8.59 and 10.56 g COD/L.d, respectively. Overall, the k values have proved that HUASB reactor had performed better than UASB reactor.